Vibrational spectroscopic characterization, quantum chemical and molecular docking studies of Valyl-Methionine dipeptide. Issue 9 (20th October 2020) - Celik, Sefa; E. Ozel, Aysen; Durak, Volkan; Akyuz, Sevim
Abstract: In this study, valyl-methionine dipeptide (Val-Met), a breakdown product of protein digestion or protein catabolism, has been investigated both theoretically and experimentally. Four different valyl-methionine conformations were formed, using the geometric parameters of two asymmetric units of L-Valine and L-Methionine, taken from the literature and their optimized geometric parameters were obtained by DFT/B3LYP level of theory, using different basis sets. The vibrational spectral analysis for the obtained two energetically most stable conformations were carried out theoretically by using 6-311++G(d, p) basis set. Experimental vibrational spectra of the title molecule were compared with the calculated spectra and the vibrational modes were assigned on the basis of potential energy distributions (PED) analysis, performed using the MOLVIB program. Furthermore, molecular electrostatic potential map analysis was carried out and dipole moment of the compound was calculated. Conformation analysis is an important step in molecular modeling. The selection of suitable conformers for many flexible drug molecules, which can be present in many conformations by turning around single bonds, to adopt different conformations, can easily be overlooked. In this work a series of dipeptide with A and B forms of valine and methionine amino acids have been chosen as examples to demonstrate the importance of conformational analysis. Energy differences between conformations underline the importance of a detailed conformational analysis and should be taken into account when defining their activities. Results show that the formation of hydrogen bonds between N1 and H17 and between H17 and O25 in Valyl(B)-Methionine(B) dipeptide, affects the stability of the molecule. The molecular electrostatic potential of the title molecule has also been calculated which is a very useful property in prediction of molecular reactive behavior. In addition, in silico molecular docking studies were performed for the title molecule with DNA. The results indicated the ability of the Val-Met dipeptide to bind DNA.